(untitled) (The Review of Diabetic Studies, 2024)
Genital tuberculosis (GTB) is a common cause of infertility in resource limited and low- and middle-income countries and although traditionally only classically few presentations are taught in medical school, the fact that GTB is a differential of several conditions, confirms it is a rarely sung but important reminder. These pre-existing conditions can be complicated in their management by the profound pharmacokinetic and pharmacodynamic (PK/PD) alterations associated with critical illness, including capillary leak, fluid resuscitation, hypoalbuminemia, enhanced renal clearance and multi‑organ dysfunction. The associated dynamic physiological alterations often make standard antimicrobial dosing regimens inappropriate, resulting in subtherapeutic exposure, treatment failure, resistance selection, or dose‑dependent toxicity. At the same time, the increased minimum inhibitory concentrations, biofilm production and persister biofilm population further downgrade antimicrobial susceptibility, leading to persisting and recurrent infections. This review identifies multi-factorial determinants of pharmacotherapy complexity in severe infectious diseases and outlines how clinical pharmacy strategies are pivotal in reducing these pressures. Core interventions consist of individualized, PK/PD‑guided dosing; therapeutic drug monitoring for narrow therapeutic index drugs; infusion optimization strategies; proactive toxicity monitoring; and pharmacist‑led medication review, with the objective of reducing drug‑related problems. Integrating clinical pharmacists as part of the multidisciplinary intensive care team and implementing clinical pharmacy services in an antimicrobial stewardship program (ASP) can reduce the number of prescribing errors, reduce adverse drug events, and reduce length of hospital stay and improve clinical outcomes. Newer methods such as model‑informed precision dosing, biomarker‑guided therapy, and artificial intelligence–informed clinical decision support provide exciting possibilities for even more individualized antimicrobial treatment. Together, pharmacy practice-based individualized pharmacotherapy directs drug exposure to a suitable quantity according to the specific biochemistry of the host, pathogen, and infection process to optimize therapeutic effectiveness while minimizing toxicity and resistance.